Echinococcosis Is Associated with the Increased Prevalence of Intestinal Blastocystis Infection in Tibetans and Host Susceptibility to the Blastocystis in Mice - Yang Zou; Yu-Gui Wang; Zhong-Li Liu; Ai-Jiang Guo; Xiao-Lu Li; Zhi-Qi Shi; Xing-Quan Zhu; Xiu-Min Han; Shuai Wang (Biology, 2022)
Blastocystis is a common human intestinal protozoan parasite. Little is known about its prevalence in echinococcosis. This study tested whether Echinococcus multilocularis infection would increase host susceptibility to Blastocystis. A total of 114 fecal samples (68 hydatid disease patients and 46 healthy people) were collected from Tibetans in the Qinghai province in China. The presence of Blastocystis was identified by sequencing of the small subunit (SSU) rRNA gene. Balb/c mice were co-infected with Blastocystis and E. multilocularis and tested for host susceptibility to Blastocystis. The overall Blastocystis prevalence was 12.3%; 16.2% in the patients and 4.4% in healthy people (p < 0.05). Sequence analysis identified three known Blastocystis genotypes, including ST1, ST2, and ST3, and one unknown genotype. Experimental dual infection significantly reduced mouse survival rate (20%), induced more severe signs, and increased intestinal damages with a higher intestinal colonization level of Blastocystis. The mouse model showed that E. multilocularis infection increases host susceptibility to Blastocystis. Our study shows a significantly higher prevalence of Blastocystis in patients with liver echinococcosis and reveals that non-intestinal E. multilocularis infection increases host susceptibility to the Blastocystis. Our results highlight that E. multilocularis infection is associated with Blastocystis. These findings remind us that more attention should be paid to the gut health of the patients with a helminth infection during clinical patient care.